Pengaruh Return on Equityi (ROE), Return on Asset (ROA), Earning periShare (EPS) terhadap Harga Saham Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia (2020 – 2022) - Sosiawan Aji Prasetya; Istiatin; Ratna Damayanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The objective of this investigation is to determine how return on equity, return on assets, and earnings per share affect the stock prices of banking companies that are listed on the Indonesia Stock Exchange (2020-2022). The population considered in the study was 47 banking companies listed on the Indonesia Stock Exchange in 2020-2022. The sample methodology employs the purposive sampling method with certain criteria. The survey included 21 banking companies. This research data uses secondary data on financial statements of banking companies. The data was analyzed using SPSS version 25's multiple linear regression. The sample is subjected to multiple linear regression analysis, a traditional assumption test. To test variables, model feasibility tests, hypothesis testing, and determination coefficient tests are employed. The research results show that equity repatriation has a significant positive impact on stock prices, asset repatriation has a significant positive impact on stock prices, and earnings per share have a significant positive impact on stock prices. The result of the decision test gives an adjusted R2 value of 0.551 or 55.1%, indicating thatistock price of banking companies is affected by the variables